(untitled) (The Journal of Psychology and Sociology, 2021)
The purpose of this article is to review contemporary foreign research on the relationship between personality traits, cinematic preferences, and film consumption (motives). The results showed that for- eign researchers, when studying the role of personality traits of viewers in the perception of film content, explaining the numerous varieties of motives and psychological needs, mainly apply the five-factor model of personality (extraversion, conscientiousness, agreeableness, neuroticism, openness to experi- ence). The results revealed a significant relationship between the prevailing personality characteristics of viewers and their film preferences, for example, viewers with high scores on benevolence, consci- entiousness and neuroticism showed a predisposition to choose popular and entertaining film genres, openness to experience was the main predictor of preference for films of auteur cinema and showed a connection with motives of artistic satisfaction, neuroticism and sensation-seeking motives were pre- dictors of preference for horror films, depending on the gender differences of the participants, “male”, “female” and gender-neutral film genres were identified, films can be used for restorative experience and mood regulation, social communication and age were important predictors of repeat viewing and film recommendations. Thus, this study highlights the importance of accounting for individual differences when examining film preferences. The results of the study will serve to expand theoretical insights and analytical possibilities for future research in the field of film psychology with a sample of Kazakhstan. Key words: basic personality traits, film preferences, five-factor model, «Вig five», media prefer-ences, film uses.